2010
DOI: 10.1186/1471-2377-10-81
|View full text |Cite
|
Sign up to set email alerts
|

Conduction in ulnar nerve bundles that innervate the proximal and distal muscles: a clinical trial

Abstract: BackgroundThis study aims to investigate and compare the conduction parameters of nerve bundles in the ulnar nerve that innervates the forearm muscles and hand muscles; routine electromyography study merely evaluates the nerve segment of distal (hand) muscles.MethodsAn electrophysiological evaluation, consisting of velocities, amplitudes, and durations of ulnar nerve bundles to 2 forearm muscles and the hypothenar muscles was performed on the same humeral segment.ResultsThe velocities and durations of the comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…When the minimum latencies of the F-wave recorded from the distal and proximal muscles in the lower and upper extremities were compared, it was found that the minimum latencies of the Fwave recorded from the proximal muscles (FUP and FPP) were longer than the minimum F-wave latencies recorded from the distal muscles (FUD and FPD). In previous studies comparing nerve conduction velocities, conduction velocity was found to be higher in proximal muscles with greater mass then the distal small muscles even they are innervated by the same nerve [6,12,13]. Considering the physiology of the Fwave, it is conceivable that the F-wave latency recorded from the proximal muscle should be shorter.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…When the minimum latencies of the F-wave recorded from the distal and proximal muscles in the lower and upper extremities were compared, it was found that the minimum latencies of the Fwave recorded from the proximal muscles (FUP and FPP) were longer than the minimum F-wave latencies recorded from the distal muscles (FUD and FPD). In previous studies comparing nerve conduction velocities, conduction velocity was found to be higher in proximal muscles with greater mass then the distal small muscles even they are innervated by the same nerve [6,12,13]. Considering the physiology of the Fwave, it is conceivable that the F-wave latency recorded from the proximal muscle should be shorter.…”
Section: Discussionmentioning
confidence: 97%
“…The reason for the higher nerve conduction velocity in the proximal segments compared to the distal segments may be the thinning of the nerve fiber diameter from proximal to distal, the shortening of the internodal segments in the nerve fibers in the distal segments, and the lower extremity temperature in the distal compared to the proximal segments [5]. If a peripheral nerve is stimulated at the same site and electrophysiological recordings are made from two different muscles located proximally and distally, it is possible to comment on the conduction parameters of nerve fibers with the same course and in the same peripheral nerve but of different diameters [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The values of CMAP amplitude from the proximal stimulus were significantly lower than those from the distal stimulus. In another trial with ulnar nerves, Oğuzhanoğlu et al [ 3 ] detected that the arm segment amplitude values were lower than the forearm segment amplitude values in the hypothenar region recordings, and authors attributed this findings to temporal dispersion. This study showed that the same findings also apply to the median nerve in addition to ulnar nerve findings.…”
Section: Discussionmentioning
confidence: 99%
“…The intensity of the stimulus was slowly increased up to the point at which the CMAP amplitude did not increase any more. Following a 25s% increase in the maximal value of stimulus, this point was determined to be the level of supramaximal stimulation [ 3 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation